Perancangan Dan Pembangunan Sistem Informasi Geografis Pemetaan Lokasi Penyedia Jasa Servis Perangkat Komputer Di Wilayah Kota Tangerang Selatan Berbasis Web - Abiyan Pasya Pamungkas; Yulianti (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
The increase in learning activities from home and working from home during the COVID-19 pandemic, of course, will also affect the increase in users of computer devices such as laptops and desktop PCs. Computer equipment service providers are services that are in great demand, especially by computer users who are new to using computer equipment during this pandemic, however, just like other business owners, MSMEs, computer equipment service providers, have also experienced a decrease in the number of customers which resulted in a decrease in turnover at the beginning of the pandemic. COVID-19 due to the lack of promotional activities during the pandemic by computer service business owners. Given these problems, the design of a geographic information system mapping the locations of computer equipment service providers is quite possible to provide convenience to people who want to make repairs to their computer equipment and assist computer equipment service providers in promoting their services, the development of this geographic information system. using the Waterfall method, and for the programming language using PHP and MySQL database.